Bebop on the Hockey Pitch: Cross-Disciplinary Creativity and Skills Transfer - Harrison, Clive M. (Frontiers in Psychology, 2016)
This paper generalises task-specific (but dissimilar) skills, from the jazz concert stage and from the hockey field, into the domain of creativity research. What is sought are clues to what skills or creativities are transferable across dissimilar domains. It is argued that certain domain-general skills are transferable across domains, but a domain-general or ‘c’ creative capacity, is not. Rather than transferring some over-arching capacity to be universally creative, this research highlights factors likely to facilitate successful cross-disciplinary creative expression and posits a correlation between the capacities for discriminant pattern-recognition, task-specific expertise, and sensory data-collection, and the transferability of creativity. Of particular significance is the capacity for informed, selective pattern-breaking based on the ‘depth’ or ‘insider’ perspective of the domain expert; such ‘expert variation and selective retention’ (EVSR) provides creative choices and responses that are likely to be perceived by the field as creative: valuable, novel and surprising. The author is a renowned Australian studio bassist, jazz musician, and music educator who also plays field hockey for Australia at Masters level. His recently completed PhD thesis, based on a performance and composition career spanning 46 years, takes the form of an analytical autoethnography drawn from personal field notes, diaries and interviews as well as published record albums.